Calculation of the thermal mode in semiconductor devices in conditions of their operation in semiconductor apparatuses - Сосков, Анатолій Георгійович; Глєбова, Марина Леонідівна; Сабалаєва, Наталія Олегівна; Форкун, Яна Борисівна (Eastern-European Journal of Enterprise Technologies, 2014)
The study of the temperature field of power semiconductor devices, operating in semiconductor apparatuses, either non-contact or hybrid was carried out in the paper. It was also shown that the main mode of the current load of power semiconductor devices, operating in semiconductor apparatuses is a pulse mode. Analytical method for calculating the values of the temperature rise in the structure of power semiconductor devices when subjected to a current pulse of arbitrary shape based on a model that adequately reflects the design of semiconductor devices was used during the studies. To calculate the thermal mode of power semiconductor devices, a technique, based on using the simplified thermal models, where the solder layers are taken into account due to expansion of thermal-resistance equivalent tungsten layers is also used. However, unlike it, the method, proposed in the paper provides a higher accuracy in calculating the temperature rise in the structure of power semiconductor devices since all layers of these devices are taken into account. Also, calculation by this method takes into account the dependence of physical properties of materials of the thyristor components on the change in their temperature. Solving the system of heat conduction equations, set up for the model that adequately reflects the thyristor design, was performed by finite difference method using the implicit scheme. When calculating the transient thermal resistance using the real model for different types of thyristors, difference in its value reaches 5 - 16% compared with the calculation using the simplified models. Thus, calculation of the temperature rise in the structure of power semiconductor devices is appropriate to carry out using the proposed method based on a model that adequately reflects the design of these devices. The described calculation method can be used for the rational choice of a power semiconductor device as a basic element of hybrid and non-contact semiconductor apparatuses in systems of their computer-aided design. The paper presents examples of calculating the thermal mode of semiconductor devices for the most common types of semiconductor apparatuses.